Artificially Intelligent Nanoarray for the Detection of Preeclampsia under Real‐World Clinical Conditions. Issue 9 (30th September 2016) - Nakhleh, Morad K.; Baram, Shira; Jeries, Raneen; Salim, Raed; Haick, Hossam; Hakim, Marwan
Abstract : Artificially intelligent nanoarray based on molecularly‐modified gold nanoparticles is tailored for the detection of preeclampsia by noninvasive breathprint analysis. The diagnostic power of the nanoarray under actual clinical conditions shows discrimination between preeclampsia and nonpreeclamptic pregnancy with an 84% accuracy, and between preeclampsia and nonpregnant women with 87% accuracy.